MiR‐197 induces epithelial–mesenchymal transition in pancreatic cancer cells by targeting p120 catenin1. Issue 6 (25th February 2013) - Hamada, Shin; Satoh, Kennichi; Miura, Shin; Hirota, Morihisa; Kanno, Atsushi; Masamune, Atsushi; Kikuta, Kazuhiro; Kume, Kiyoshi; Unno, Jun; Egawa, Shinichi; Motoi, Fuyuhiko; Unno, Michiaki; et al.
Abstract Invasive ductal adenocarcinoma (IDA) of the pancreas manifests poor prognosis due to the early invasion and distant metastasis. In contrast, intraductal papillary mucinous adenoma or carcinoma (IPMA or IPMC) reveals better clinical outcomes. Various molecular mechanisms contribute to these differences but entire picture is still unclear. Recent researches emphasized the important role of miRNA in biological processes including cancer invasion and metastasis. We previously described that miR‐126 is down‐regulated in IDA compared with IPMA or IPMC, and miR‐126 regulates the expression of invasion related molecule disintegrin and metalloproteinase domain‐containing protein 9 (ADAM9). Assessing the difference of miRNA expression profiles of IDA, IPMA, and IPMC, we newly identified miR‐197 as an up‐regulated miRNA specifically in IDA. Expression of miR‐197 in pancreatic cancer cells resulted in the induction of epithelial–mesenchymal transition (EMT) along with the down‐regulation of p120 catenin which is a putative target of miR‐197. Direct interaction between miR‐197 and p120 catenin mRNA sequence was confirmed by 3′UTR assay, and knockdown of p120 catenin recapitulated EMT induction in pancreatic cancer cells. In situ hybridization of miR‐197 and immunohistochemistry of p120 catenin showed mutually exclusive patterns suggesting pivotal role of miR‐197 in the regulation of p120 catenin. This miR‐197/p120 catenin axis could be a novel therapeutic target. J. Cell. Physiol. 228: 1255–1263, 2013. © 2012 Wiley Periodicals, Inc.